Genetic causes of sudden cardiac death in children: inherited arrhythmogenic diseases. Issue 5 (October 2017) - Vacanti, Gaetano; Maragna, Riccardo; Priori, Silvia G.; Mazzanti, Andrea
Abstract : Purpose of review: In this chapter we will discuss the most recent and relevant evidences published in the field of inherited arrhythmogenic disorders, focusing on the so called 'channelopathies' that are associated with sudden cardiac death (SCD) in children: long QT syndrome (LQTS), short QT syndrome (SQTS), Brugada syndrome (BrS), and catecholaminergic polymorphic ventricular tachycardia (CPVT). Recent findings: We will discuss the latest diagnostic criteria for channelopathies released by the European Society of Cardiology, the new data on BrS in children and the recent evidence supporting a genotype-specific therapy for LQTS type 3. Moreover, we will present further insights into the risk stratification of the children affected by LQTS, analyzing the role of imaging for the prediction of life-threatening arrhythmias. In addition, we will offer a perspective on how to deal with genetic results in families affected by SCD at very young ages. Summary: The selected publications will aid pediatricians in their clinical work when managing little patients with inherited arrhythmias, providing the most recent information for diagnosis, risk stratification, and management.